Analisis Efektivitas Dan Kontribusi Pajak Hotel Dan Restoran Terhadap Pendapatan Asli Daerah Kabupaten Jepara Tahun 2012-2020 - Fahriatul Hidayah; Jalu Aji Prakoso (Tirtayasa Ekonomika, 2022)
The purpose of this study is to analyze the effectiveness of Hotel and Restaurant Tax receipts in Jepara Regency in 2012-2020 and to analyze the contribution of Hotel and Restaurant Taxes to Regional Original Income (PAD) in Jepara Regency in 2012-2020. quantitative. The data is obtained from the Regional Financial and Asset Management Agency of Jepara Regency in the Report on the Realization of the Jepara Regency's Budget Revenue from 2012 to 2020. The data analysis used is an analysis of effectiveness and contribution analysis. Results Based on this research, it can be concluded that the average effectiveness of Hotel Tax and Restaurant Tax receipts in Jepara Regency in 2012-2020 is 125% which is said to be very effective. Meanwhile, the average contribution of Hotel Tax and Restaurant Tax revenue to Regional Original Income (PAD) in Jepara Regency in 2012-2020 is 1,4%, thus it is said to be quite contributing (CB).